The JURIDICIAL PROBLEMS RELATED TO THE REGULATION OF THE DURATION OF PATERNITY LEAVE FOR PRIVATE WORKERS WHEN THE WIFE GIVES BIRTH - Selvira, Sisca Riski; Binti Ahmad, Nur Ain Adlin (Indonesian Journal of Labour Law and Industrial Relations, 2025)
Paternity leave for private workers in Indonesia is still regulated in a limited manner in the legislation, which is only 2 to 3 days in duration as stipulated in Law Number 13 of 2003 concerning Manpower and Law Number 4 of 2024 concerning Maternal and Child Welfare. This duration is considered inadequate to provide optimal support to wives who give birth and in childcare. This study aims to analyze the urgency of regulating the duration of paternity leave for private workers and to examine the form of paternity leave arrangements for private workers in Indonesia. This research uses normative juridical methods with statutory, conceptual, historical, and comparative approaches and uses prescriptive analysis techniques. The results show that the limitations of paternity leave have an impact on family welfare, father's involvement in parenting, and the balance between work and family life. Compared to other countries, such as Singapore and Malaysia, which have implemented paternity leave policies with longer durations, Indonesia is still lagging behind in providing protection for male workers' rights to accompany their wives in childbirth. Therefore, labor policy reform is needed to extend the duration of paternity leave for private sector workers to create a better balance between workers' rights and family needs.